Refleksi Diri Guru Praktikan dalam Proses Pembelajaran Berdiferensiasi Mata Pelajaran Bahasa Indonesia - Ramadhini, Nove Amelya Jihan; Sukmawan, Sony (STAI Auliaurrasyidin Tembilahan, 2024)
A differentiated learning approach is one way to realize the concept of Merdeka Curriculum. In its application, there are discrepancies that have an impact on meeting the learning needs of students. Therefore, a self-reflection step is needed to find the discrepancies that occur. This research uses a descriptive qualitative method with observation, interviews, and documentation on two practicing teachers and a master teacher at SMPN 14 Malang. Data were analyzed using the Miles and Huberman technique through data reduction, data presentation, and conclusion drawing. The interview results showed that the implementation of content, process, and product differentiation was not perfect due to the short tenure of the practicing teacher, poor planning, and misunderstanding of the differentiation concept. Observations showed that the learning atmosphere was not conducive, and students' enthusiasm was low. This study found weaknesses in differentiated learning planning and suggested expanding learning media, improving teaching techniques, and mapping students' learning needs through self-reflection.